Drone Delivery Problems and Drone applicability - Rabe, Jannes (2020)
Rising traffic congestion, increasing air pollution and increasing customer expectations are major challenges for the urban last mile delivery. Drones are unmanned aerial vehicles (UAV) that can bring relief to the urban delivery sector. UAV applications are recently gaining more publicity and companies are pushing the applications of drones in the last mile delivery. The main motivation for implementation is the opportunity of reducing the delivery cost and delivering items faster. Optimal route planning for a set of customers that have to be served by the UAV makes the delivery more efficient and cost-saving. In this dissertation, a practical application is proposed as Drone Delivery Problems and solved with a written python script based on the Google OR-Tools that calculates the sequence of customers that minimizes the distance travelled and satisfies the additional constraints. Three different scenarios (Travelling Salesman Problem, Vehicle Routing Problem and Capacitated Vehicle Routing Problem) display the capability of the software to find optimal results. The python script does find an optimal solution to all nine proposed problems within a certain time limit and without ending in a near-optimal solution. The second area of research in this thesis is the investigation of the applicability of current UAV technology in supply chain operations. Most importantly, the UAV environment has to be adjusted to the needs of this new delivery option. Laws and regulations are holding back innovative ideas and, in most countries, commercial UAV use is not permitted.